Implementation and Validation of Anatomic Triplane Hallux Abducto Valgus Classification. Issue 3 (11th September 2017) - Santrock, Robert; Smith, W. Bret; Dayton, Paul; Hatch, Daniel
Category: Bunion Introduction/Purpose: The most common classification system for HAV deformity is based on two-dimensional radiographs. This system relies upon measurements taken of the transverse plane. (IMA and HVA) to classify and deploy surgical options based on the severity of these angles [1]. Recently, the understanding of HAV deformity as a three-dimensional problem has been described. A study by Kim et al. [2] utilized WB-CT to describe a frontal plane rotational component in 87% HAV cases. To develop a better understanding of HAV, a unique anatomic classification system (see figure) was proposed. The aims of this study were: (1) To use traditional WB radiographs to confirm the findings of Kim's WB-CT study. (2)To use inter-observer and intra-observer analysis to validate the classification of HAV into this new system. Methods: An Institutional Review Board approved multi-center retrospective study was performed utilizing four view WB radiographs (Anterior-Posterior, Oblique, Lateral and Axial Sesamoid) on patients presenting to the clinic for "bunion, " Hallux Valgus, HAV, Hallux Rigidus or "great toe pain." The data were analyzed for the presence of frontal/coronal plane rotation of the first metatarsal, subluxation of the sesamoids, metatarsus adductus and degenerative joint disease of the first MTP (metatarsophalangeal) joint (Hallux Rigidus); these findings were compared to Kim's study. Additionally, these data were used to categorize HAV deformities into a new 3D classification scheme and were tested for inter-observer and intra-observer reliability. Results: The results established the presence of frontal/coronal plane rotation and subluxation in similar ratios as reported by Kim et al. thus confirming the utility of a four-view WB radiograph series in recognition of 3D deformity of HAV. The results also confirmed good reliability of the classification from both the inter-observer and intra-observer standpoint. Conclusion: These data suggest that new protocols and tools are reliable in helping the surgeon recognize and better identify the three-dimensional components of HAV.